2015
DOI: 10.5152/akd.2014.5536
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of plasma catestatin concentrations with metabolic and vascular parameters in untreated hypertensive patients: Influence on high-density lipoprotein cholesterol

Abstract: Objective:Catestatin has several cardiovascular actions, in addition to diminished sympatho-adrenal flow. Decreased plasma catestatin levels may reflect a predisposition for the development of hypertension and metabolic disorders. We planned to investigate the possible roles of catestatin in untreated hypertensive patients. As a secondary objective, we compared catestatin concentrations of healthy subjects with those of hypertensive patients in order to understand whether catestatin is increased reactively or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
4
21
1
12
Order By: Relevance
“…In the present study, BMI, hypertension, and CAD type were independently related to the plasma catestatin level in multivariate linear regression. The results are in accordance with a separate recent report [21]. However, as previous studies have reported, plasma catestatin levels may change over time following an acute MI; therefore, the timing of blood sample collection may influence the measured levels of catestatin.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, BMI, hypertension, and CAD type were independently related to the plasma catestatin level in multivariate linear regression. The results are in accordance with a separate recent report [21]. However, as previous studies have reported, plasma catestatin levels may change over time following an acute MI; therefore, the timing of blood sample collection may influence the measured levels of catestatin.…”
Section: Discussionsupporting
confidence: 82%
“…In humans, whose plasma CST levels vary from 0.33 nmol/L to 1.5 nmol/L, the levels of CST are not only diminished in the case of essential hypertension but are also diminished in normotensive individuals with a positive family history for hypertension (14). Furthermore, low conversion of CgA to CST is associated with increased mortality in patients hospitalized with acute heart failure (14), and low plasma CST levels also correlate with low plasma levels of cholesterol-rich HDL particles (15). In the current study, we investigated the role of CST on hepatic MF recruitment and function as well as on regulation of obesity-induced hepatic inflammation and IR.…”
mentioning
confidence: 99%
“…Catestatin promotes lipolysis and fatty acid oxidation however the relative potencies of the variant and wild-type forms have not been studied [35]. [36] Sahu et al speculated that catestatin involvement in the process of gluconeogenesis and lipolysis might vary in potencies for both forms of catestatin [4]. That and the attenuated catecholamine levels in CHGASer364 carriers would cause their elevated triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…That and the attenuated catecholamine levels in CHGASer364 carriers would cause their elevated triglyceride levels. Recently a positive correlation between plasma catestatin and HDL levels has been reported [36]. …”
Section: Discussionmentioning
confidence: 99%